Pengembangan Ekowisata Melalui Pendekatan Ekonomi Kreatif di Desa Kindingan Kecamatan Hantakan Kabupaten Hulu Sungai Tengah - Noorsyifa, Gusti; Hidayah, Sri; Syahla, Mayang Effiena; Noorfallah, Ananda; Sauki, Ahmad; Hermawan, Rio; Nasuha, Habibi Adam; Dewi, Tiara Kusuma; Hanifah; Salma, Ratu; Ardanata, Stevany Nike (Prodi Sosiologi FISIP ULM, 2025)
Kindingan Village has a population of 719 people with a percentage of 99% earning a living as farmers and planters. The condition of the community that is too dependent on nature in any aspect over time turns into a serious problem. In the past few years, problems have often occurred, one of which is that several times the community has experienced crop failure which has a huge impact on them. This is caused by extreme weather and the season that is always transitional. Therefore, the service team proposed a program inspired by the potential of basket weaving skills by the Kindingan Village community which was then implemented into a program called “Rumah Kreatif”. Where we as a team of servants conducted the formation of basket production groups and socialization of online marketing with the community. The program implementation applied a participatory approach. In an effort to build community participation, the service team applies the live-in method, which is living in the village during the implementation of the service and actively involved in community activities outside of the service program. The duration of the program implementation is 58 days, starting from July 18, 2024 to September 13, 2024. The results achieved from the implementation of this service program are the creation of new jobs outside the agricultural sector, so that it is expected to increase income. Long-termimpact is expected in the form of improving the village economy through the sustainability of creative businesses managed by the local community.